Voices of the Travelers: Analyzing Foreign Tourists' Experiences in Santa Fe, Bantayan, Cebu - Olivar, Gladies Mae (Transpublika Publisher, 2024)
This study's qualitative-exploratory research design aimed to explore the experiences of foreign visitors to Santa Fe, Bantayan Cebu, Philippines, using a researcher-made interview guide. The study was undertaken at Santa Fe, Bantayan, Cebu, Philippines, with seven (7) randomly chosen foreign visitors. The narratives of the research informants were subjected to thematic analysis. The themes created for the reasons that prodded the foreign visitors to visit Santa Fe, Bantayan Island, Cebu, Philippines are Propensity to do Business in Santa Fe, Cebu, Enjoying the Natural Endowed Beauty, Leisure and Relaxation: Common Reasons for Tourists’ Visit, and Connecting and Reconnecting Through Visiting Friends, while the theme emanated for the factor of the length of stay of the foreign visitors in Santa Fe Bantayan Island, Cebu, Philippines is Multifaceted Considerations to Stay. Finally, on the themes relating to how foreign visitors adapt to the culture, language, food, climate, and political ambiance in Santa Fe, Bantayan Island Cebu, Philippines are Kindness, Friendly and Hospitality: Primordial to Culture Adaptation in the Philippines, Tourists’ Ease in Communicating the Local People, Filipinos Are English Speakers: Boosting Tourism Industry, Foreign Tourists Love the Local Food, and Sun, Sand, and Sea: Impetus for an Enjoyable Vacation. This study suggests that the local government should promote tropical island tourism by focusing on the 3-S (sea, sun, and sand) and emphasizing Santa Fe, Bantayan's unique features to set it apart from other tourist destinations.